Bankruptcy Prediction Using The Atlman Z-Score Modification Method In Mining Sector Companies For The 2018-2022 Period - Yuliana; Ari Ardiana Sapari; Nardi Sunardi (Indonesian Development of Economics and Administration Journal, 2023)
.  In this study, the aim was to explore the tendency for company bankruptcy in the mining sector in Indonesia in the 2018-2022 period on the Indonesia Stock Exchange using the Altman Z-Score model. The research sample was taken from financial reports that were routinely published during that period. The results show that the Altman Z-Score model can identify the tendency of bankruptcy in the mining company sector on the Indonesia Stock Exchange. The results of the research analysis show that the three mining sector companies that were tested and registered on the IDX in the 2018-2022 period had an average value of Z≥ 2.9, which is 1,205, which indicates a bankrupt financial state. However, these companies still need to continue to improve their performance in order to gain profits in order to avoid the risk of bankruptcy.